Application of Operational Research in Sustainable Environmental Management and Climate Change - Mukesh Kumar Mishra (ZBW – Leibniz Information Centre for Economics, 2020)
Today, the impact of OR can be felt in many areas. A large number of management firms are currently engaged in OR activities. The principles of operational research (OR) and related mathematical methods have been applied to environmental issues for the long times. However, the increasing pressures experienced by industry over the last decade, pertaining to sustainable development performances, have renewed interests and intensified the potential application of OR techniques in environmental management. Capacity decisions establish a set of conditions within which operations will be required to function. Hence, it is extremely important to include input from operations management people in making capacity decisions. There is need to develop a balance between modernization and sustainability. Sustainability refers to service and production processes that use resources in ways that do not harm ecological systems that support both current and future human existence. Sustainability measures often go beyond traditional environmental and economic measures to include measures that incorporate social criteria in decision making. Because they all fall within the realm of operations, operations management is central to dealing with these issues. The need for effective optimisation methods that incorporate concepts of efficient resource use and environmental concern is becoming more and more urgent as the environmental situation deteriorates. This paper focus on the possibilities of incorporating Operational Researchers with environmental issues and the importance of OR models and techniques in environmental management.
Keywords: 330; Operation Research; Sustainable Development